Exploring the effect of lifestyle behaviors and socioeconomic status on atrial fibrillation: the mediating role of 91 inflammatory cytokines - Liu, Yiheng; Huang, Mingsheng; Sun, Yue; Dai, Weiran (Frontiers in Cardiovascular Medicine, 2024)
Atrial fibrillation (AF) is one of the most prevalent cardiac arrhythmias with significant economic and social burden. Whether it is associated with lifestyle behaviors and socioeconomic status is currently poorly understood. This study aimed to explore the relationship among these factors and to determine the role of inflammatory cytokines.We investigated the causal effects of lifestyle behaviors and socioeconomic status on AF by bidirectional, two-sample Mendelian randomization (MR). Instrumental variables (IVs) were obtained from a publicly available genome-wide association study (GWAS). A two-step MR was conducted to determine the mediating role of 91 inflammatory cytokines. Inverse-variance-weighted (IVW) was used as the main method with four supplementary MR methods. To obtain more robust results, several sensitivity analyses were conducted.The results indicated that 7 of the lifestyle behaviors (smoking initiation, vegetable intake, coffee consumption (cups/d), dozing, lifetime smoking index, napping, alcohol abuse) were potential risk factors for AF. One socioeconomic status (Education attainment (years of education) was causally associated with decreased risk of AF. Moreover, we found that Thymic stromal lymphopoietin levels, CD40L receptor levels, C-X-C motif chemokine 6 levels, C-X-C motif chemokine 11 levels mediated the causal effect, at proportions of 13.6%, 4.1%, 4.3%, and 6.9%, respectively.Our findings provide insight into the relationship between lifestyle behaviors, socioeconomic status, and AF. Inflammatory cytokines are potential mediators on this relationship.